Influence of different polyether sulfone substrate of thin-film composite forward osmosis membrane on neodymium rejection - Yeoh, Yuan Xin; Mazrul Nizam, Abu Seman; Mohd Yusri, Mohd Yunus; Mohammad, Abdul Wahab; Mohd Hashim, Mohd Saad (Elsevier, 2025)
Technology to treat rare earth element (REE) upstream and midstream wastewater especially acid mine drainage (AMD) is urged to be developed as it was proven current circular economy practice in downstream processes is environmentally unfriendly. This study applied forward osmosis (FO) to treat synthetic AMD containing neodymium (Nd) by using a thin-film composite (TFC) membrane as it is cheaper compared to other membrane technologies that require external pressure. Non-solvent induced phase separation (NIPS) was used to fabricate porous substrate prepared from different polyether sulfone (PES) concentrations (13 wt%, 15 wt%, 17 wt%,19 wt%) and 10 wt% PVP. Then, interfacial polymerization (IP) was done on the substrate for crosslinking of polyamide (PA) thin-film active layer. Intrinsic parameters of the fabricated TFC membranes were studied using a two-stage non-pressurized test. The occurrence of the electric double layer effect was proven in this study which was accountable for the Nd rejection together with the structure of the PA layer. TFC membrane prepared from 15 wt% PES showed the best Nd rejection efficiency with 98.28 % in ALFS orientation due to its high negative surface charge with the PA structure of leaves and nodules.